Peran Public Relations dalam Mengatasi Manajemen Krisis: Studi Kasus Public Relations Officer Lion Air Group - Ignes Ambarwati; Mochammad Mirza; Ari Suseno; Alamsyah Alamsyah (Master Manajemen, 2024)
PT. Lion Mentari Airlines (Lion Air) was founded on November 15 1999 and began operations on June 30 2000. By serving flight routes from Jakarta to Pontianak using Boeing 737-200 type aircraft. Lion Air has a philosophy that consumers are truly sovereign (consumer sovereignty) with the slogan "We make people fly". On one of the social media platforms which is currently in the spotlight for the wider community, namely Tiktok, there is a report that has attracted the attention of netizens about the derailment of one of the planes from the Batik Air airline, which is a subsidiary of the Lion Group, the Jakarta - Yogyakarta flight, which occurred at the airport. Adisujipto Yogyakarta. The method used in this research is the qualitative case studies research method. This research was carried out using 2 techniques, the first was collecting data by observing the phenomenon of events that occurred on social media, and the second was by conducting direct interview techniques with related sources. You can find out how alert the Lion Air Group public relations officer is in dealing with issues and problems developing in society to anticipate crises that occur in the company or airline. Writing the conclusion is the final part of the research paper which contains a common picture and ties it into the initial research. Writing a conclusion involves having to give a very brief description of the results, although you don't need to go into too much detail in the presentation.